2001
DOI: 10.1159/000054691
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of <i>Dexras1</i> Expression by Endogenous Steroids

Abstract: Dexras1, a newly identified member of the Ras superfamily of proteins, was discovered in AtT-20 corticotrope cells because its expression was induced in response to glucocorticoids (dexamethasone; Dex). As yet, the function of Dexras1 is unknown, but its rapid induction in response to glucocorticoids suggests the possibility that it may be involved in negative feedback regulation of corticotropin secretion. To better understand the control of Dexras1 expression, possible effects of other steroid hormones on it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…We also treated HEK293 cells transfected with FE65-APP GAL4-dependent reporter constructs with dexamethasone because Dexras1 was first identified as a dexamethasone-induced protein (36,55,56). After dexamethasone treatment, FE65-APP signaling was inhibited, which is in line with the result we observed from transfection of Dexras1 (Fig.…”
Section: Dexras1 Binds To Fe65supporting
confidence: 84%
See 1 more Smart Citation
“…We also treated HEK293 cells transfected with FE65-APP GAL4-dependent reporter constructs with dexamethasone because Dexras1 was first identified as a dexamethasone-induced protein (36,55,56). After dexamethasone treatment, FE65-APP signaling was inhibited, which is in line with the result we observed from transfection of Dexras1 (Fig.…”
Section: Dexras1 Binds To Fe65supporting
confidence: 84%
“…Dexras1 is a member of the Ras superfamily of GTPases and was originally identified as a dexamethasone-inducible gene (36,55,56). Although Dexras1 is a GTPase, it possesses several differences from other Ras members.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the regulation of Rasd1 expression in these tissues. To date, the only factors known to regulate Rasd1 expression are glucocorticoids [16,25,26] and estrogens [9,26]. Therefore, in this study we determined whether other agents, especially mitogens that affect pituitary cell proliferation, affect Rasd1 mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these findings suggest the existence of a regulatory loop in which stimulation of adenylyl cyclase/cAMP enhances its own activity and production by inhibiting Rasd1 expression. Estrogen is effective in stimulating Rasd1 mRNA expression in vivo in mouse pituitary tissues [26]. Our previous study using DNA microarray analysis and qRT-PCR demonstrated that E2 stimulates Rasd1 mRNA expression in primary cultures of rat pituitary cells [9].…”
Section: Discussionmentioning
confidence: 99%
“…Observations of note in this regard are the dramatic, tissue-specific, upregulation of AGS1 by dexamethasone in cultured cells and the intact animal (Brogan et al, 2001;Kemppainen and Behrend, 1998;Kemppainen et al, 2003) vida infra), the growth suppression observed upon AGS1 overexpression in some but not all cell types, the down-regulation of AGS1 (RASD1) in breast ductal carcinoma in situ (Abba et al, 2004), and changes in AGS1 mRNA during the circadian cycle in specific brain areas (Table 2). Glucocorticoids have diverse effects in the body and certainly play important roles in development and cell differentiation and it is interesting to suggest that some of their effects may be due to induction of AGS1 expression (Graham et al, 2001).…”
Section: Regulation Of Ags1mentioning
confidence: 99%